(untitled) - Grisham, John (New York, 2001)
A couple has decided to not celebrate Christmas and go on a cruise, only to discover that skipping Christmas brings enormous consequences.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy